Predicting ethical values and training needs in ethics - Callan, Victor J. (Journal of business ethics, 1992)
Two hundred and twenty-six state employees completed a structured questionnaire that investigated their ethical values and training needs. Top management were more likely to have attitudes against cronyism and giving advantage to others. Individuals higher in the organizational hierarchy, and female employees were more likely to believe that discriminatory practices were an ethical concern. In addition, employees with a larger number of clients outside of the organization were more supportive of the need to maintain strict confidentiality in business dealings. Employees' awareness and use of the organization's code of conduct generally proved to be poor predictors of ethical values. Other analyses revealed that a variety of sociodemographic factors, job characteristics and ethical values predicted specific areas of training needs in ethics.